Faktor - Faktor Yang Mempengaruhi Kejadian Insomnia Di Wilayah Kerja Puskesmas Patikraja Kabupaten Banyumas - Maisharoh, Rizka; Purwito, Dedy (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: Identifying the correlation among age, educational level, income level, lifestyle, psychological factors, physical illness, marital status, and the environment with insomnia occurrence on elderly in the working area of Puskesmas Patikraja,Banyumas Regency. Method: This research is a quantitative descriptive research using the cross-sectional method. The sample was 99 elderly taken through cluster random sampling. Data were analysed using the chi-square statistical test and continued with logistic regression test. Results: Most of the respondents belong to early elderly with 53 respondents (53.5%), the educational level of elementary school with 66 respondents (66.7%), the income level of Rp. 1,589,000.00 with 62 respondents (62.6%), the marital status of widow/ widower with 52 respondents (52.5%), physical illness with 62 respondents (62.6), psychological factors of normal stress with 76 respondents (76.8%), comfortable environment with 55 respondents (55.6%), healthy lifestyle with 52 respondents (52.6%). Among the result, it is found that lifestyle becomes the most affecting factors of insomnia occurrence on the elderly, in which the value of Exp (B) is 16.577. Conclusion: Elderly must pay attention to a healthier lifestyle so that they can reduce the risk of insomnia occurrence.